ASSOCIATION BETWEEN FUNCTIONAL AEROBIC CAPACITY AND SCOLIOMETER-MEASUREMENT SPINAL DEVIATION IN ELEMENTARY SCHOOL STUDENT: AN IMPLICATION FOR EARLY PHYSIOTHERAUPETIC INTERVENSION - Martha Sri Astuti; Irine Yunila Prasetyawati; SR. Ignata Yuliati SSpS (Nurse and Holistic Care, 2026)
Background: Early detection of spinal deformities of school-aged students is an important component of early musculoskeletal assessment and physiotherapeutic prevention in school-aged children.  A scoliometer measurement 5-7° considered as a positive screening indicator for developing scoliosis and may potentially affect physical function, including functional aerobic capacity. Objective: The aim of this study is to examine the association between functional aerobic capacity and scoliometer-measured spinal deviation among elementary school students. Methods: Using cross-section design, the study was conducted among 47 fifth-grade students selected through systematic random sampling.  Spinal rotation was assessed by spinal rotation angle deviation using scoliometer.  Functional aerobic capacity was measured using the Incremental Shuttle Walk Test (ISWT).  ISWT performance was categorized based on predicted values.  Data were analyzed using Spearman’s correlation with a significance level of p < 0.05. Results: Eighty-seven percent of students showed a 5° spinal rotation (positive scoliosis screening). Most deviations were located in the lumbar region (73%).  The majority of students demonstrated below-average to above average aerobic capacity.  Female students had higher mean ISWT distances than males.  Spearman analysis revealed a very weak positive correlation (r=0,180) that was not statistically significant (p=0.227). Conclusion: There is no significant association between spinal deviation angle and functional aerobic capacity in this population.  Early scoliosis screening remains essential to support early musculoskeletal assessment and physiotherapeutic prevention in school-aged children.